2018
DOI: 10.31234/osf.io/m5cwq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Moral Standing of Animals: Towards a Psychology of Speciesism

Abstract: We introduce and investigate the philosophical concept of ‘speciesism’ — the assignment of different moral worth based on species membership — as a psychological construct. In five studies, using both general population samples online and student samples, we show that speciesism is a measurable, stable construct with high interpersonal differences, that goes along with a cluster of other forms of prejudice, and is able to predict real-world decision-making and behavior. In Study 1 we present the development an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(69 citation statements)
references
References 17 publications
5
63
1
Order By: Relevance
“…In the second wave (undertaken 5 weeks after the initial testing) follow-up participants completed only the MESx to examine test-retest reliability. In line with recent research [ 15 ] we estimated a follow-up response rate on Mechanical Turk of approximately 40%. Therefore, to ensure an adequately sized wave two sample (at least 200 based on sample size conventions for an estimated effect size between 0.6 and 0.8; [ 16 ]), we aimed for a sample of approximately 600 in wave one.…”
Section: Methodsmentioning
confidence: 54%
“…In the second wave (undertaken 5 weeks after the initial testing) follow-up participants completed only the MESx to examine test-retest reliability. In line with recent research [ 15 ] we estimated a follow-up response rate on Mechanical Turk of approximately 40%. Therefore, to ensure an adequately sized wave two sample (at least 200 based on sample size conventions for an estimated effect size between 0.6 and 0.8; [ 16 ]), we aimed for a sample of approximately 600 in wave one.…”
Section: Methodsmentioning
confidence: 54%
“…As also no influence of reactance was found, future studies need to further investigate the underlying mechanisms which make defaults more effective. One possible direction could be to include the psychological construct of speciesism which has been shown to predict meat consumption (Caviola et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This has a negative impact on people's health, animal welfare, and the environment (e.g., Foer, ; Raphaely & Marinova, ; Tilman & Clark, ; Walker et al, ). A growing body of research on the psychological construct of speciesism, that is the allocation of different moral value based on the species one belongs to, helps to explain the reasons why people continue to eat meat (Caviola, Everett, & Faber, ). For example, people who attribute less mental attributes to animals are more likely to eat meat (Bastian, Loughnan, Haslam, & Radke, ; Loughnan, Bastian, & Haslam, ).…”
Section: Introductionmentioning
confidence: 99%
“…While speciesism has typically been defined as taking place when humans believe that they have intrinsically more value, worth, and dignity relative to individuals of other species (Herzog, Grayson, & McCord, ; Singer, ), this general notion has recently been found to predict the differentiation that humans make among different types and species of animals per se. Indeed, Caviola, Everett, and Faber () have shown that speciesism predicts such a differentiation, and more specifically people's willingness to allocate time or money to other humans and also to “superior” animals (such as dogs) relative to “inferior” animals (such as pigs). Yet, and given that the notion of speciesism generally applies to the superiority of humans relative to all animal types (see also Herzog et al, ), the phenomenon whereby we distinguish among and organize cognitively different species and types of animals—within the large category of nonhuman animals—remains to be operationalized and empirically captured.…”
Section: Differences In Attitudes Toward Animalsmentioning
confidence: 99%
“…By separating these types of animals in our minds and evaluating and also treating them very differently, the nature of our interactions and the quality of the relationship we have with these animals are likely to change drastically (Amiot & Bastian, ). While these differences in attitudes and treatment across animal types and species are paradoxical and can be considered as immoral (Bastian & Loughnan, ; Serpell, ), they are common and present in our everyday interactions with animals (Caviola, Everett, & Faber, ). To better understand the cognitive mechanism behind these observed differences, in the current research, we investigate how humans manage to keep different animal types separated in their minds, specifically through the phenomenon of compartmentalization.…”
mentioning
confidence: 99%